Migration patterns of the Japanese sardine in the Sea of Japan by combining the microscale stable isotope analysis of otoliths and an ocean data assimilation model - Aono, Tomoya; Sakamoto, Tatsuya; Ishimura, Toyoho; Takahashi, Motomitsu; Yasuda, Tohya; Kitajima, Satoshi; Nishida, Kozue; Matsuura, Takayoshi; Ikari, Akito; Ito, Shin-ichi (Frontiers in Marine Science, 2024)
The Japanese sardine (Sardinops sagax melanostictus) is a small pelagic fish found in the Sea of Japan, the marginal sea of the western North Pacific. It is an important species for regional fisheries, but their dispersal and migration patterns during early life stages remain unclear. In this study, we analyzed the stable oxygen isotope ratios of otoliths of young-of-the-year (age 0) Japanese sardines collected from the northern offshore and southern coastal areas of the Sea of Japan in 2015 and 2016. The ontogenetic shifts of the geographic distribution were estimated by comparing the profiles of life-long isotope ratios and temporally varying isoscape, which was calculated using the temperature and salinity fields produced by an ocean data assimilation model. Individuals that were collected in the northern and southern areas hatched and stayed in the southern areas (west offshore of Kyushu) until late June, and thereafter, they can be distinguished into two groups: one that migrated northward at shallow layer and one that stayed around the southern area in the deep layer. A comparison of somatic growth trajectories of the two groups, which was reconstructed based on otolith microstructure analysis, suggested that individuals that migrated northward had significantly larger body lengths in late June than those that stayed in the southern area. These results indicate that young-of-the-year Japanese sardines that hatched in the southern area may have been forced to choose one of two strategies to avoid extremely high water temperatures within seasonal and geographical limits. These include migrating northward or moving to deeper layers. Our results indicate that the environmental variabilities in the southern area could critically impact sardine population dynamics in the Sea of Japan.